Efektifitas Berbagai Dosis Bio-Slurry Sebagai Bumbu Kompos Terhadap Waktu Pembentukan dan Kualitas Kompos di Dusun Gadingharjo, Donotirto, Kretek, Bantul - Catur Bunga Novitamala; Bambang Suwerda; Indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Organic waste yielded from households in Gadingharjo Village have not been yet treated pro-perly. The utilization that can be implemented is composting. One of activators that can accele-rate the processing time and improve the quality of the compost is bio-slurry. The aim of this research is to know the effectiveness of bio-slurry as compost activator by conducting a post-test-with-control-group designed experiment. The amount of domestic waste that was treated were 75 kg and were obtained with non-random sampling technique. The time of composting formation were counted from the initial process until the compost were mature, based on the following criteria: blackish brown color, soiled smells, and has environment stable temperature. The measurement of N, P, and K substance were carried on at the laboratory of BBTKL Yogya-karta. In the control group, the mean composting time was 34,7 days, meanwhile in the treat-ment groups of 1:1:2; 1:1:3 and 1:1;4 it was 25,3 days, 27,3 days, and 29,7 days. The result of one way anova test obtained p value < 0,001 which is meant that the differences were signifi-cant. The average of N, P, and K concentrations in the control group were 1,0438 %; 0,1880 %; and 1,4045 %. Meanwhile, in treatment group of 1:1:2 they were: 1,4639 %; 0,2699 %; and 1,2320 %; in treatment group of 1:1:3 they were: 1,0465 %; 0,2707 %; and 1,3154 %; and in treatment group of 1:1:4 they were: 0,8865 %; 0,2285 %; and 1,2992 %; respectively. To con-clude, bio-slurry can be used as an activator to speed-up the composting time and to improve the compost quality. The most effective bio-slurry addition is 1:1:2 ratio .